Dissolved Oxygen Concentration From the Water around the Floating Cage Fish Culture Area and from the Area with No Cage, in the DAM site of the Koto Panjang Reservoir - Nia Anggraini; Asmika H. Simarmata; Clemen Sihotang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
AbstractIn floating cage fish culture activities, degradation of feed remain and fish feces willincrease the Dissolved Oxygen content in the surrounding area. A research aims to understandthe Dissolved Oxygen concentration in the water from the cage area and from the area that hasno cage has been done from July - November 2014. In the Koto Panjang Dam, the floating cagefish culture is in the DAM site. Samplings were conducted 4 times, once/ 2 weeks. In There were3 stations, namely 200 m upstream nof the cage area (S1), in the cage area (S2) and 200 mdownstream of the cage area (S3). each station, water samples were collected from 3 differentdepth, surface; 2 secchi and 4 secchi depths. Parameters measured were dissolved oxygenconcentration, phytoplankton, free carbon dioxide, nitrate, phosphate, temperature, pH,transparancy, and depth. Result shown the concentration of Dissolved Oxygen in the S1 was 4,52mg/L – 7,17 mg/L; in the S2 was 3,28 mg/L – 6,57 mg/L; and in the S3 4,00 mg/L – 6,87 mg/L.The highest concentration of the Dissolved Oxygen was in the upstream (S1) while the lowestwas in S2. Other water quality parameter measured were phytoplankton: 500 cells/L – 8,226cells/L; free carbon dioxide: 4,49 mg/L - 11,48 mg/L; temperature: 30,6oC – 31oC; pH: 5;transparancy 1,98 m – 2,55 m; depth: 27 m – 40 m. General the parts quality still support theaquatic organism life. the values of water quality parameters indicate that the water quality in theDAM site of the Koto Panjang is good and might be able to support the life of aquatic organismsin that area.Keywords: Dissolved Oxygen, cage fish culture, Koto Panjang Dam